Integrative Effects of Vine Water Relations and Grape Ripeness Level of Vitis vinifera L. cv. Shiraz/Richter 99. I. Physiological Changes and Vegetative-Reproductive Growth Balances - Hunter, J.J.; Volschenk, C.G.; Novello, V.; Strever, A.E.; Fouché, G.W. (South African Journal of Enology and Viticulture, 2016)
The water relations and physiological status of the grapevine are critical for obtaining a quality product and for fully exploring vineyard and grape potential. The objective of this investigation was to determine the effect of grapevine water status (induced by means of two field water capacity-based irrigation levels, 75% and 100%, applied at single and combined vine developmental stages) on morphological and physiological changes in Vitis vinifera L. cv. Shiraz/Richter 99 grapevines and grapes (harvested at different soluble solid levels) under field conditions. The integrative effects of vine water relations and grape ripeness level, specifically in a Mediterranean high winter rainfall area, have not yet been investigated systematically. The terroir affected the reaction of the vines to treatments. The soil displayed high water-holding capacity and a buffer against favourable evapotranspiration conditions, even with a western aspect and being subjected to long and relatively dry seasons, with frequent occurrence of high temperatures and grapevines with fully developed canopies. The vines did not seem overly stressed – in line with the relatively high base soil water fractions of mostly more than 50% of field water capacity. Primary and secondary leaf water potential and stem water potential displayed similar patterns and the water potential of the primary and secondary leaves was similar. Despite relatively high base soil water contents that prevented excessively low plant water potential and classic leaf and berry behaviour to surface, the vines still responded in a noticeable way to volume and timing of irrigation in relation to the grape ripeness level status. Water relations, ripeness level and terroir conditions showed an integrated, steering impact on physiological, vegetative and reproductive behaviour. Post-véraison irrigated vines were expected to maintain relatively high water potential during the last weeks of the ripening period, but this seemed not to be the case. All vines seemed to have recuperated/stabilised during this time, maintaining their water balances. Physical, physiological and compositional changes in the berry during late ripening under field conditions were clarified further. New information was obtained on the relationships between the behaviour of the root system, canopy and grapes and the changing terroir conditions during the ripening period.